2021
DOI: 10.3389/fmicb.2021.700142
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Biocontrol of Cucumber Fusarium Wilt by Combined Application of New Antagonistic Bacteria Bacillus amyloliquefaciens B2 and Phenolic Acid-Degrading Fungus Pleurotus ostreatus P5

Abstract: Continuous monoculture of cucumber (Cucumis sativus L.) typically leads to the frequent incidence of Fusarium wilt caused by Fusarium oxysporum f. sp. cucumerinum (FOC). As potent allelochemicals, phenolic acids are believed to be associated with soilborne diseases. This study aimed to investigate the effect of single or co-inoculation of antagonistic bacteria Bacillus amyloliquefaciens B2 and phenolic acid-degrading fungus Pleurotus ostreatus P5 on the suppression of cucumber Fusarium wilt. The strain B2 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Currently, few varieties of cucumber are resistant to Fusarium wilt. Traditional treatments such as chemical pesticides and soil fumigation cause environmental pollution, increase pathogen resistance, and decrease product safety. , Control measures such as grafting and root replacement and rotation are effective. However, the cumbersome operation and the large workload along with high costs are limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, few varieties of cucumber are resistant to Fusarium wilt. Traditional treatments such as chemical pesticides and soil fumigation cause environmental pollution, increase pathogen resistance, and decrease product safety. , Control measures such as grafting and root replacement and rotation are effective. However, the cumbersome operation and the large workload along with high costs are limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was reported that Bacillus could act as a fungal inhibitor through the production of lipopeptides, various extracellular enzymes and protein-like substances, and VOCs [ 53 , 54 , 55 ]. We investigated the various types of antimicrobial substances that may be produced by strain SBB.…”
Section: Discussionmentioning
confidence: 99%
“…The PGPR Bacillus amyloliquefaciens B2 was isolated from the rhizosphere soil of a healthy cucumber plant [5] and stored in Luria-Bertani (LB) medium (10 g L −1 peptone, 5 g L −1 yeast extract, 10 g L −1 NaCl and 20 g L −1 agar) at 4 • C. Pleurotus ostreatus strain P5 was isolated from spent mushroom (P. ostreatus) substrate [27]. The fungal isolate was maintained on potato dextrose agar (PDA) slants at 4 • C.…”
Section: Microbial Culture and Chemicalsmentioning
confidence: 99%
“…In addition, several studies have demonstrated that white rot fungi are also beneficial to the growth of plants by enhancing biological nitrogen fixation [23,24], soil phosphorus mobilization [25] and the amelioration of salinized soils [26]. In a recent study [5], we reported that the combined application of the PGPR Bacillus amyloliquefaciens B2 and the plant beneficial white rot fungus Pleurotus ostreatus P5 can significantly increase the growth of cucumber under continuous cropping conditions. However, the effect of P. ostreatus P5 on the secondary metabolites of B. amyloliquefaciens B2 is unclear, especially the production of CLPs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation